Dual functional PDMS sponge SERS substrate for the on-site detection of pesticides both on fruit surfaces and in juice. Issue 11 (15th May 2018) - Sun, Ji; Gong, Lin; Lu, Yuntao; Wang, Dongmei; Gong, Zhengjun; Fan, Meikun
Abstract : A versatile dual-functional polydimethylsiloxane (PDMS) sponge Surface Enhanced Raman Scattering (SERS) substrate has been fabricated for the on-site detection of pesticide residues both on the surface and in solution with minimum or no sample pretreatment. Abstract : In this study, a versatile dual-functional polydimethylsiloxane (PDMS) sponge Surface Enhanced Raman Scattering (SERS) substrate has been fabricated for the on-site detection of pesticide residues both on the surface and in solution with minimum or no sample pretreatment. The PDMS sponge was fabricated using white granulated sugar and soft white sugar as pore-forming reagents. Later, multiple rounds of Ag NP deposition were performed by incubating the PDMS sponge in the Ag NP solution with the help of 3-mercaptopropyltrimethoxysilane (APTMS). The highest SERS enhancement was achieved through 2 rounds of Ag NP deposition. Under optimum conditions, with Rhodamine 6G (R6G) as the probe molecule, the limit of detection (LOD) reached 2 femtomoles (20 μL at a concentration of 100 pM). The analytical performance for potential on-site applications of the substrate has been demonstrated with pesticide-spiked agricultural products taken as examples. Without sample pretreatment, the pesticide triazophos and methyl parathion were successfully detected by swabbing on the fruit surface with LODs of 0.79 ng and 1.58 ng, respectively. In addition, the lowest detected concentrations of triazophos and methyl parathion in fruit juice were found to be 100 ppb and 1 ppm. More importantly, the PDMS sponge SERS substrate can be safely stored for 36 days without affecting its SERS activity.